RDNA-09. RADIATION PRIMES SB28 GLIOBLASTOMA FOR RESPONSE TO TGFβ AND PD-L1 NEUTRALIZING ANTIBODIES - Borrero Garcia, Luis; Reiners, Oliver; Gonzalez-Junca, Alba; Okada, Hideho; Helen Barcellos-Hoff, Mary (Neuro-oncology (Charlottesville, Va.), 2019)
Abstract SB28 is a new luciferase expressing murine glioblastoma (GBM) cell line whose morphology, growth pattern, mutational burden immune infiltrate more closely resembles human GBM and is unresponsive to immunotherapy (OncoImmunology, 7:12, e1501137). Radiation therapy (RT) has the potential to improve response to combinations by multiple means: cell kill that may activate an immune response, effects on vascular system may improve drug access, induction of DNA damage that can be augmented by targeted or chemotherapy, and modulation of the tumor microenvironment. High transforming growth factor β (TGFβ) activity in most GBM, which increases with radiation, likely opposes effective therapy by endorsing an effective DNA damage response and being immunosuppressive. Here evaluated the response of SB28 to radiation in combination with PD-L1 checkpoint blockade or neutralizing TGFβ. Establishment of intracranial tumors was monitored by bioluminescence. We determined that SB28 endogenously activate TGFβ as evaluated by biomarkers. We used radiolabeled antibodies and PET-CT to demonstrate access to intracranial tumors, indicative of a compromised blood-brain barrier. TGFβ neutralizing antibody, 1D11, had little effect on tumor growth compared to mice receiving IgG control antibody (median survival control: 19 days vs 1D11: 20.5 days). A single dose of radiation of 10 Gy delivered to the tumor site increased median survival to 21 day, which was increased to 31 days in mice treated with 1D11. In a second experiment in which the radiation dose was 6 Gy, 1D11 provided no benefit. In contrast, median survival of mice treated with PD-L1 neutralizing antibodies 3 days after being irradiated with 6 Gy demonstrated increased median survival (Control: 18 day; anti-PD-L1 20.5; RT: 25 days; RT + anti- PD-L1: 28 days). Double treatment resulted in 1/7 long term survival and loss of bioluminescence indicative of tumor elimination. Thus, radiation can prime SB28 GBM for response to biological agents.